ChemInform Abstract: Difluorocarbene Addition to Alkenes and Alkynes in Continuous Flow. Issue 39 (September 2016) - Rulliere, Pauline; Cyr, Patrick; Charette, Andre B.
Abstract: A scalable difluorocyclopropanation of a broad range of alkenes is developed, including alkyl and aryl 1‐substituted, 1, 1 and 1, 2‐disubstituted as well as trisubstituted derivatives.